Development of a palm-sized bioelectronic sensing device for protein detection in milk samples - Mahapatra S.; Chandra P. (My University, 2025)
The present study relates a portable optical sensing device supported by a small single-board (SBC) computer. The electronic architectural avenue connects the SBC with a camera, LED lights and a monitor. A ‘sensor integration unit’ has been linked with the device where the biological reactions were performed and assessed based on the concentration-dependent optical signal outputs. This setup can detect the generation of colors and distinguish their changes in the RGB intensity scale with an accuracy of a single pixel unit. A predefined range of values was obtained and fed to the device that can quantitatively sense the molecule of interest on the sensing matrix. The device has a touchscreen interactive panel that allows users to manually set experimental conditions and connect the entire measurement process to the cloud storage for backup information. We have considered detecting Alkaline Phosphatase (ALP) quantitatively from standard solutions as well as in milk samples as a proof-of-concept protein molecule. The device has shown exceptional analytical performance for lower and higher concentration ranges (0–100 U/mL and 100–1000 U/mL) with correlation coefficient values of 0.99. The detection limit of ALP was determined to be 0.1 U/mL, and the average time of a sample assessment was recorded to be 15 s. The device has also been tested against ALP-spiked milk samples to check its effectiveness and commercial viability. The outcome of the real-time assessment was sensitive and efficient, indicating its direct commercial and clinical importance towards colorimetric detection for diverse macromolecules. © 2022